2020
DOI: 10.3897/mycokeys.67.52716
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and toxigenicity of fungi and description of Fusarium madaense sp. nov. from cereals, legumes and soils in north-central Nigeria

Abstract: Mycological investigation of various foods (mainly cowpea, groundnut, maize, rice, sorghum) and agricultural soils from two states in north-central Nigeria (Nasarawa and Niger), was conducted in order to understand the role of filamentous fungi in food contamination and public health. A total of 839 fungal isolates were recovered from 84% of the 250 food and all 30 soil samples. Preliminary identifications were made, based on macro- and micromorphological characters. Representative strains (n = 121) were studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 92 publications
7
19
1
Order By: Relevance
“…Among the metabolites were 16 mycotoxins and other metabolites produced by several fungal genera including, but not excluded to, Aspergillus , Alternaria , Fusarium and Penicillium . The spectrum of fungal metabolites detected in the food samples agree with the diversity of moulds recovered from the foods, except for a few classes of compounds whose fungal producers were not recovered—again, owing possibly to the limitations of the applied culture-dependent mycological analysis (Ezekiel et al 2020a ).…”
Section: Resultssupporting
confidence: 58%
“…Among the metabolites were 16 mycotoxins and other metabolites produced by several fungal genera including, but not excluded to, Aspergillus , Alternaria , Fusarium and Penicillium . The spectrum of fungal metabolites detected in the food samples agree with the diversity of moulds recovered from the foods, except for a few classes of compounds whose fungal producers were not recovered—again, owing possibly to the limitations of the applied culture-dependent mycological analysis (Ezekiel et al 2020a ).…”
Section: Resultssupporting
confidence: 58%
“…Aspergillus aflatoxiformans was recovered from all the foods, but mostly in the cereals. This agrees with a previous report from Nigeria, wherein A. aflatoxiformans predominated in cereals including maize and rice [3]. Aspergillus aflatoxiformans (previously, wrongly classified as A. parvisclerotigenus), has been reported in cassava from neighbouring Benin Republic [46], as well as dried mushroom and peanuts from Nigeria [47,48].…”
Section: Discussionsupporting
confidence: 91%
“…In this study, Fusarium was not recovered from any of the food samples, which agrees with findings from two previous studies conducted in Nigeria on rice [2] and pupuru [12]. Conversely, this finding from the present study contradicts other available reports [3,34,39,40] that reported several Fusarium species in cereals including rice and maize. Penicillium was the second most predominant genus in the food samples, occurring in all the foods and mostly in maize and pupuru.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations